Status Seeking Taxpayer and Tax Evasion - Sugata Marjit; Koushik Hati; Lei Yang (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper explores whether tax compliance would be affected if the tax payers are "status" seekers. If relative income is a symbol of relative status in a society, status concerned individuals would evade paying taxes more relative to the case where status is not a concern. However, such an outcome would not hold if the symbol of relative status is relative consumption of the "status" good and not relative income. We generalize the scenario by introducing a measure of relative status which depends on both relative income and consumption of the status good.
Keywords: H26; D31; D91; O15; H21; 330; status-seeking behavior; tax evasion; relative income; conspicuous consumption; Inequality